Analisis Kepuasan Orang Tua Siswa Dalam Layanan Pendidikan di Madrasah Ibtidaiyah Nurul Huda Kota Dumai - Syawal Simatupang (Jurnal Pendidikan Tuntas, 2025)
This study aims to analyze the level of parental satisfaction with educational services at Madrasah Ibtidaiyah (MI) Nurul Huda Dumai City. The research employed a descriptive method with both quantitative and qualitative approaches. Data were collected through questionnaires distributed to 46 parents as samples using a random sampling technique. The research instrument was developed based on service quality dimensions (SERVQUAL), specifically focusing on three main dimensions: reliability, assurance, and tangibles. The results of the data analysis indicated that the parental satisfaction level reached 75%, which falls into the "Satisfied" category. The findings revealed that the school has provided good services through teacher discipline, student quality assurance programs (such as Al-Qur'an memorization), and adequate facilities and infrastructure.